Bailey's industrial oil & fat products - Bailey, Alton Edward, 1907-1953 (John Wiley & Sons, 2005)
The Sixth Edition features seventy-five articles that synthesize and present the latest information available on products, processing and equipment, technology and by-products. The theory and practice of handling, formulating and isolating oils and fats, as well as analytical methods and uses, are all covered. Plus, the information and background needed for the development of new products and applications are also provided. Moreover, all the latest topics are presented, including new articles on fungal and algal oils, conjugated linoleic acid, cocoa butter, phytosterols, and plant biotechnology used in oil production.